Incidence and predictors of second-line antiretroviral treatment failure among adults living with HIV in Amhara region: a multi-centered retrospective follow-up study - Muluneh Alene (BMC Infectious Diseases, 2019)
Abstract Background Second-line Antiretroviral Therapy (ART) regimens are used when patients develop treatment failure for first-line drug regimens. It is costly unaffordable and it is not widely available for patients in resource limiting setting, there is a need to maximizing the duration of stay on second-line regimen. This study was conducted to estimate the incidence rate of second-line treatment failure and to identify its predictors among adults living with HIV in the Amhara region. Methods An institution based retrospective follow-up study was conducted from May to June 2017. A total of 1,011 adults on second-line ART who were enrolled between February 2008 and April 2016 were included for final analysis. Kaplan-Meier estimator curves were used to describe the survival function. Semi-parametric proportional hazard model was fitted to identify the predictors of treatment failure. Results The overall incidence of second-line treatment failure was 9.86 per 100 person-years. It was high during the first and the last year of follow-up. The rate of second-line treatment failure was higher for patients who didn’t change second-line regimens (HR: 1.55, 95%CI: 1.18–2.04), who had poor ART adherence (HR: 1.40, 95%CI: 1.06–1.85), and not taking INH (HR: 1.68, 95%CI: 1.23–2.30) as compared to their counter group. The rate of treatment failure for patients who were under WHO clinical stage III at switch (HR: 0.68, 95%CI: 0.50–0.91) was also lower as compared to clients who were under WHO clinical stage I. Furthermore, the rate of treatment failure was higher for clients who were under second-line regimen “TDF-3TC-LPV/r” (HR: 1.55, 95%CI: 1.03–2.32) and “AZT-3TC-LPV/r” (HR: 3.00, 95%CI: 1.86–4.85) as compared to patients under “ABC-ddI-LPV/r” regimens. Conclusions A high incidence rate of second-line treatment failure was noticed in the study setting. The rate of second-line treatment failure was higher for patients who didn’t change drug regimens, who had poor ART adherence, and who were not taking INH. Therefore, addressing significant predictors to prevent treatment failure among ART patients is essential and sustainable monitoring to reduce the risk of treatment failure is also desirable.